The really important thing is not to live, but to live well. A discussion about euthanasia, autonomy and self-respect - Aguayo Westwood, Pablo (Acta Bioethica, 2020)
This paper aims to introduce the notion of self-respect in the context of the discussion on euthanasia. First, I briefly show two features that characterize much of the contemporary moral debates on issues of applied ethics, features that will allow me to explain more clearly the discussion about euthanasia. Looking back at the history of Philosophy, in the second part, I will show how Plato offered one of the first reflections on the difference between the mere fact of being alive (to zen) and living well (to eu zen), and whose arguments we can use to discuss euthanasia. Third, I will examine what we understand by a person and how a particular comprehension of this notion will all